ASEAN Non-Intervention Principles: An Alternative Settlement towards Human Rights Violation in Rohingya - Yulianto Achmad; Nanik Prasetyoningsih; M. Reformis Al Fath (Jurnal Media Hukum, 2021)
The frame of international news is colored with a series of systemic and consistent human rights violation experienced by the Rohingya ethnic group in Burma. Toward this case, it is unlikely for Burma to be willing and to be able to resolve this case internally. Hence, as a regional security and stability guard in the Southeast Asia region, ASEAN should take part in settling human rights violations that occur in its member states. However, every settlement attempted by ASEAN is constantly distracted with Non-Intervention Principles. This research aims to examine the alternative ideas for Non-Intervention Principles of ASEAN as a settlement towards human rights violation on Rohingya ethnic. This research used normative research, based on the secondary data was employed as the research method. The obtained data were analyzed by using qualitative analysis. The research found that the Non-Intervention principle has been applied in ASEAN in the most rigid form. Meanwhile, Humanitarian Assistance and Humanitarian Intervention mechanism is an alternative settlement towards human rights violations on the Rohingya ethnic group in Myanmar